The Palaearctic types of Chrysididae (Insecta, Hymenoptera) deposited in the Linsenmaier collection. Part 3. Elampini: genus Hedychrum Latreille - Rosa, Paolo; Heim, René; Bernasconi, Marco Valerio (Zootaxa, 2022)
An illustrated catalogue of the Palaearctic types of species and subspecies described by Walter Linsenmaier in the genus Hedychrum Latreille, 1802 is given. Linsenmaier described 14 taxa of Hedychrum; almost all primary types are deposited in the collection, at the Natur Museum (Luzern, Switzerland), with the exception of two holotypes which are deposited at the Natural History Museum (London), and Naturalis (Leiden). Hedychrum mithras Semenov-Tian-Shanskij, 1967 spec. resurr. is revalidated from the previous synonymy with Hedychrum luculentum bytinskii Linsenmaier, 1959. A list of the species described and pictures of the holotypes and allotypes deposited in the collection are given.